Propagation prediction and measurement on outdoor wireless LAN 2.4 ghz applications at Universiti Teknologi Malaysia - Elchakwi, Saleh Yousif (2008)
Propagation prediction and measurement has become the most important step in designing and implementing an outdoor Wireless Local Area Network (WLAN). It leads to the necessity of a sound and precise radio network planning tools. The objectives of this project are to give practical study on the losses of the signal strength which is affecting the coverage and to compare between the measurement and the prediction of the received signal strength. In this project, three-dimensional (3-D) software known as the Advanced Topographic Development and Image (ATDI) has been used to predict the signal strength in outdoor environment then the measurement of the signal strength was conducted by using the AirMagnet software. The area of the measurement and the prediction was chosen at Universiti Teknologi Malaysia (UTM) campus which is Kolej Tun Hussien Onn (KTHO). After that, it was divided into three scenarios. The carrier frequency which is being used is the unlicensed band 2.4 GHz (IEEE 802.11g) and at the transmitter end omni directional antenna has been used. The results of the comparison show a great amount of agreement between the measurement and prediction. It also gives a clear explanation about the effect of the building and trees on the design performance.